Utilizing Optimization Technique in the Formulation and Development of Snacks for Public Secondary School Students of the Philippines - Obsequio-Namoco, Sarah I.; Namoco, Rhoda A.; Namoco Jr., Consorcio S. (Pakistan Journal of Nutrition, 2015)
Due to limited allowance, students buy food primarily because it is cheap and delicious. The nutrient contents of the food are the least that they consider. This study proposes snack item that will meet the buying capacity of the students at the same time meeting the nutritional and palatability value of the food. In order to do this, a linear programming diet model is used to develop a model recipe for snacks that would meet the energy requirement for the growing up years of adolescents. This study involved 1364 adolescent participants from various public high schools of East II District of Cagayan de Oro City, Philippines in order to examine the sources of income of their parents, daily allowance allotted for their snacks in school, their prevalent food choices and the reasons for such food choice. Based on the survey, the average allowance of the students for snacks is PhP 6.00-10.00 (USD 0.13-0.22) per day. Results of the LP model provide modified recipes for fried banana spring roll with ingredients rich in calories, fats, carbohydrates and protein. Upon sensory acceptability test, respondents confirmed a very desirable rating for the new recipes developed. The recipes are recommended to be produced among school canteens to meet the nutritional needs of students at cost affordable to them.